Spectrophotometric Methods for Determination of Tranexamic Acid and Etamsylate in Pure Form and Pharmaceutical Formulation. Issue 1 (2015) - Mohamed, Gehad G.; Frag, Eman Y.Z.; Sedeek, Abeer A.
No abstract available